(untitled) (PerCursos, 2022)
The Brazilian Semiarid is a space endowed with natural singularities, potentialities and limitations, which in its essence comprise landscapes of scenic beauties with high potential to Geodiversity. It is in that context that this work aims to analyze how geoparks, through Geodiversity, can foster the territorial development of the Brazilian semiarid region. Therefore, this research was systematized in three main stages: bibliographic survey, systematic integrative review of the literature on Geodiversity and Geodiversity & Brazilian Semiarid Region, and secondary data collection. The concept of Geodiversity is relatively new and integrates a number of other themes, being intimately linked to the abiotic elements of the terrestrial space, especially geological and geomorphological expression. In turn, Geoparks as territorial units demarcated by the presence of unique geological-geomorphological heritage of high value in their diversity and applications, can enable the territorial development of the places that shelter these singularities. In that sense, it is understood that Geodiversity through Geoparks can promote the territorial development of the Brazilian Semiarid, as it enables a series of satellite activities, such as Geotourism.